2020
DOI: 10.3389/fpsyt.2020.565291
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity Is Associated With Increased Levels of Anxiety, Depression, and Stress in Brazilians During the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Objective: To evaluate the levels of anxiety, depression, and stress associated with the practice of physical exercise (PE) during pandemic by COVID-19. Methods: This study has a cross-sectional characteristic and was carried out between May 12 and 14, 2020. An online questionnaire was applied with questions to assess sociodemographic characteristics and physical exercise during the CoVID-19 pandemic, in addition to depression, anxiety, and stress analysis. The study was appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
57
5
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 49 publications
9
57
5
6
Order By: Relevance
“…Furthermore, previous studies have focused on the importance of physical exercise during the COVID-19 confinement (Chtourou et al, 2020 ; Jiménez-Pavón et al, 2020 ). In this regard, our results are consistent with a previous cross-sectional study, which reported that those people who were not enrolled in physical exercise during the COVID-19 confinement showed a higher level of stress, anxiety, and depression (Silva et al, 2020 ). Moreover, same as this study, another one conducted a randomized controlled trial focused on the effects of a home-based resistance training on the physical fitness of older adults.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, previous studies have focused on the importance of physical exercise during the COVID-19 confinement (Chtourou et al, 2020 ; Jiménez-Pavón et al, 2020 ). In this regard, our results are consistent with a previous cross-sectional study, which reported that those people who were not enrolled in physical exercise during the COVID-19 confinement showed a higher level of stress, anxiety, and depression (Silva et al, 2020 ). Moreover, same as this study, another one conducted a randomized controlled trial focused on the effects of a home-based resistance training on the physical fitness of older adults.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was supported by studies conducted in Turkey, the United Kingdom, and Brazil. 34–36 This might be due to engaging in physical activity regularly is a healthy habit and a protective factor against diseases and harmful risk behaviors. Performing physical activity provides several benefits like improving self-esteem and body image, decreasing stress and nervous tension, improving motor balance, and favoring social relatedness.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity and sedentary behaviors are favored by the measures adopted to curb the consequences of the coronavirus disease (COVID-19) [ 12 , 13 , 14 ], such as social distancing, ranging from isolation, quarantine, local confinement up to lockdown. The COVID-19 disease emerged in December 2019 in China and rapidly reached several countries [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the outbreak of COVID-19 had a strong impact on people’s daily life, including the level of PEx and PA, because people reduced daily activities outside. As a logical consequence, this situation impacted the general health of the population and contributed to physical inactivity [ 13 , 14 , 17 ] and also to undesirable psychological conditions, such as insecurity and fear causing anxiety and stress [ 13 , 16 , 18 ], thoughts about death, feelings of helplessness and abandonment [ 18 ], especially for the elderly.…”
Section: Introductionmentioning
confidence: 99%